Coated lithium secondary battery positive electrode active material, coating forming solution, method for producing coated lithium secondary battery positive electrode active material, lithium secondary battery
Patent Information
- Application Number
- JP2025058508
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本発明の一態様によれば、全固体電池に適用でき、高電位で充電した場合でも電池容量が低下することを抑制できる、被覆付きリチウム二次電池用正極活物質を提供することができる。
Smart Images

Figure 2026165879000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a positive electrode active material for a coated lithium secondary battery, a coating forming solution, a method for producing a positive electrode active material for a coated lithium secondary battery, and a lithium secondary battery. [Background technology]
[0002] In recent years, with the widespread use of portable electronic devices such as mobile phones and laptop computers, there has been a strong demand for the development of small, lightweight lithium-ion batteries with high energy density. Furthermore, there is a strong demand for lithium-ion batteries with high energy density for use in electric vehicles.
[0003] In recent years, all-solid-state batteries have attracted attention as lithium-ion secondary batteries that meet these requirements. All-solid-state batteries consist of a positive electrode layer, a solid electrolyte layer, a negative electrode layer, etc., and are expected to be put into practical use in aspects such as high energy density, high output, high voltage, and high stability compared to conventional batteries that use electrolytes (solutions) such as organic solvents.
[0004] However, current all-solid-state batteries are not sufficient in terms of both output characteristics and high-voltage tolerance. One of the reasons for this is the formation of a high-resistance layer at the contact interface between the solid electrolyte and the positive electrode active material.
[0005] For example, Patent Document 1 discloses an invention that aims to provide an electrode body capable of reducing interfacial resistance. Patent Document 1 discloses an electrode body characterized by containing a positive electrode active material having an active material and a first solid electrolyte covering 70% or more of the surface of the active material, and a second solid electrolyte. Patent Document 1 also discloses that the first solid electrolyte is lithium niobate and the second solid electrolyte is a sulfide.
[0006] However, with regard to lithium secondary batteries using the electrode body disclosed in Patent Document 1, there were cases where the battery capacity decreased when charged at a high potential. [Prior art documents]
Patent Documents
[0007]
Patent Document 1
Summary of the Invention
Problem to be Solved by the Invention
[0008] In view of the problems of the above-described prior art, the present invention aims to provide a coated positive electrode active material for lithium secondary batteries that is applicable to all-solid-state batteries and can suppress a decrease in battery capacity even when charged at a high potential.
Means for Solving the Problem
[0009] In order to solve the above problem, according to one aspect of the present invention, There is provided a coated positive electrode active material for lithium secondary batteries for use in the positive electrode of an all-solid-state battery, wherein the electrolyte is a solid electrolyte. The positive electrode active material has a layered crystal structure, and a coating disposed on the surface of the positive electrode active material. The coating includes a first region containing lithium carbonate and a second region containing lithium silicate, thereby providing the coated positive electrode active material for lithium secondary batteries.
Effects of the Invention
[0010] According to one aspect of the present invention, it is possible to provide a coated positive electrode active material for lithium secondary batteries that is applicable to all-solid-state batteries and can suppress a decrease in battery capacity even when charged at a high potential.
Brief Description of the Drawings
[0011] [Figure 1] Figure 1 is a schematic cross-sectional view of a coated positive electrode active material for lithium secondary batteries according to one aspect of the present disclosure. [Figure 2] Figure 2 is a schematic cross-sectional view of a lithium secondary battery. [Modes for carrying out the invention]
[0012] The embodiments for carrying out the present invention will be described below with reference to the drawings, but the present invention is not limited to the embodiments described below, and various modifications and substitutions can be made to the embodiments described below without departing from the scope of the present invention. [Active material for coated lithium secondary batteries] The coated lithium secondary battery positive electrode active material of this embodiment (hereinafter also referred to as "coated positive electrode active material") can be used in the positive electrode (positive electrode layer) of an all-solid-state battery in which the electrolyte is a solid electrolyte.
[0013] Schematic cross-sectional diagrams of the coated positive electrode active material 10 of this embodiment are shown in Figures 1(A) and 1(B). Note that Figures 1(A) and 1(B) are merely schematic diagrams and do not accurately represent the shape, size, scale, etc. Therefore, the cross-sectional shape of the coated positive electrode active material 10A, coated positive electrode active material 10B, and the particles of the positive electrode active material 11 is not limited to a circular shape, but can have any shape. Furthermore, the coating 12 does not need to have a constant thickness. The coated positive electrode active material 10B shown in Figure 1(B) is a modified example of the coating 12 configuration, and will be explained primarily using Figure 1(A), with Figure 1(B) used as needed.
[0014] As shown in Figure 1(A), the coated positive electrode active material 10 of this embodiment may have a positive electrode active material 11 and a coating 12 disposed on the surface of the positive electrode active material 11.
[0015] The following describes each component contained in the coated positive electrode active material 10 of this embodiment. (1) Positive electrode active material The positive electrode active material 11 contained in the coated positive electrode active material of this embodiment can be any positive electrode active material that can insert and remove lithium (Li) by electrochemical reaction.
[0016] The positive electrode active material 11 preferably has a layered structure, that is, a layered crystal structure. This is because a positive electrode active material having a layered crystal structure can particularly enhance output characteristics when applied to a lithium secondary battery. When the positive electrode active material has a layered crystal structure, the positive electrode active material may have a layered rock salt type structure (α-NaFeO₂ type structure) or the like.
[0017] The positive electrode active material 11 can contain, for example, nickel and cobalt.
[0018] Examples of the positive electrode active material 11 include composite oxides containing, for example, lithium, nickel, and cobalt. Examples of the positive electrode active material 11 include composite oxides containing lithium (Li), nickel (Ni), cobalt (Co), and element M (M) at a substance amount ratio of Li:Ni:Co:M = a:x:y:z. Here, a, x, y, and z may satisfy x+y+z=1 and 0.8≦a≦1.2. x and y can be selected such that the sum with z is 1, and may satisfy 0<x<1 and 0<y<1. The element M can be at least one selected from the group consisting of manganese (Mn), magnesium (Mg), aluminum (Al), titanium (Ti), iron (Fe), copper (Cu), zinc (Zn), zirconium (Zr), niobium (Nb), molybdenum (Mo), tantalum (Ta), and tungsten (W). Since the element M is an optional additive element, z can satisfy 0≦z<1.
[0019] The above composite oxide can be represented by the general formula: Li a Ni x Co y M z O 2+α . In the general formula, α preferably satisfies -0.2≦α≦0.2. Since x, y, z, a, and the element M in the general formula have already been described, the description thereof will be omitted.
[0020] Note that the positive electrode active material 11 contained in the coated positive electrode active material 10 of the present embodiment may be a mixture of a plurality of types of positive electrode active materials having different compositions.
[0021] As described above, it is preferable that the positive electrode active material 11 contains at least cobalt (Co). The inclusion of cobalt in the positive electrode active material 11 makes it easier to stabilize the structure of the positive electrode active material 11 during charging and discharging, thereby preventing deterioration of the positive electrode active material 11 when the battery is used at high voltage.
[0022] The structure of the positive electrode active material described above can be identified by analytical techniques such as X-ray diffraction and electron diffraction. The molar ratios of the elements contained in the positive electrode active material can be determined by analytical techniques such as X-ray fluorescence analysis and ICP (Inductively Coupled Plasma) emission spectroscopy.
[0023] The shape of the positive electrode active material is not particularly limited. For example, it may be positive electrode active material particles having an average particle diameter of several nanometers to several tens of micrometers and having the form of primary particles or secondary particles formed by aggregation of primary particles, or it may be a thin film positive electrode film. An example of a thin film positive electrode film is a positive electrode film deposited by the PLD (pulsed laser deposition) method. (2) Covering The covering 12 may include a first region 121 and a second region 122.
[0024] Furthermore, the first region 121 can contain lithium carbonate. The second region 122 can contain lithium silicate.
[0025] Furthermore, the first region 121 may consist solely of lithium carbonate. Also, the second region 122 may consist solely of lithium silicate. However, this does not rule out the possibility of unavoidable impurities in either case.
[0026] The arrangement of the first region 121 and the second region 122 is not particularly limited; they just need to be positioned on the surface of the positive electrode active material 11.
[0027] For example, as shown in Figure 1(A), a single layer of coating 12 may be placed on the surface of the positive electrode active material 11, and a first region 121 and a second region 122 may be placed within the single layer of coating 12. The first region 121 and the second region 122 may be regularly arranged within the coating 12, or they may be randomly arranged. The first region 121 and the second region 122 may have the same thickness, or they may be different. Also, the area that the first region 121 and the second region 122 cover on the surface of the positive electrode active material 11 may be the same, or they may be different.
[0028] As shown in Figure 1(B), a layer of the first region 121 and a layer of the second region 122 may be arranged on the surface of the positive electrode active material 11. In Figure 1(B), the layer of the first region 121 and the layer of the second region 122 are arranged in order from the position closest to the positive electrode active material 11, but the configuration is not limited to this. For example, the layer of the second region 122 and the layer of the first region 121 may be arranged in order from the position closest to the positive electrode active material 11. Furthermore, the number of layers of the first region 121 and the second region 122 is not particularly limited; each may consist of one layer, or multiple layers may be included.
[0029] The coating 12 only needs to cover at least a portion of the surface of the positive electrode active material 11. However, it is preferable that the area ratio of the area covered by the coating 12 to the surface of the positive electrode active material 11 be as high as possible. (2-1) Composition and properties of the first and second regions (1st area) Region 121 may contain lithium carbonate. The elements contained in region 121 can be analyzed by EELS (Electron Energy Loss Spectroscopy) or EDX (Energy Dispersive X-ray Spectroscopy), etc. Furthermore, the compounds contained can be identified from the elements contained and their elemental proportions.
[0030] By including the first region 121 in the coating 12, when applied to a lithium secondary battery, the electron conductivity between the positive electrode active material 11 and the solid electrolyte can be increased, thereby improving the output characteristics.
[0031] The first region 121 may contain an amorphous phase of lithium carbonate. By making the material contained in the first region 121 amorphous (non-crystalline), the electronic conductivity can be particularly enhanced, and the positive electrode resistance in the lithium secondary battery can be particularly reduced.
[0032] The amorphous nature of the material contained in the first region 121 can be confirmed, for example, by performing electron diffraction on the first region 121 and observing that no crystal spots are observed.
[0033] Specifically, for example, the following procedure can be used to evaluate whether the substance contained in the first region 121 is crystalline or amorphous. First, the coated positive electrode active material 10 to be evaluated is embedded in resin or the like, and then a sample for cross-sectional observation is prepared by performing focused ion beam processing (FIB). Then, the location of the first region 121 is identified by TEM (Transmission Electron Microscope) observation of the cross-sectional observation sample, and, if necessary, by EELS measurement or EDX measurement. Next, electron diffraction measurement is performed on the identified first region 121, and if no crystal spots are observed in the obtained diffraction pattern, it can be evaluated that the substance contained in the first region 121 is amorphous. In this case, a halo pattern may also be observed in the diffraction pattern. If crystal spots are observed in the obtained diffraction pattern, it can be confirmed that the substance contained in the first region 121 is crystalline, i.e., has crystallinity.
[0034] Furthermore, multiple methods may be used in combination to observe the coating 12, such as surface observation using an SEM (Scanning Electron Microscope) and cross-sectional observation using a TEM. For example, information such as the elemental distribution on the surface of the coated positive electrode active material 10 can be obtained using SEM-EDX and used when identifying the first region 121 and the second region 122 in the cross-sectional TEM image. (Second area) Region 2, 122, may contain lithium silicate. The elements contained in region 2, 122, can be analyzed by EELS, EDX, electron diffraction, etc.
[0035] The second region 122 may contain a crystalline phase of lithium silicate. Therefore, the lithium silicate contained in the second region 122 can also be identified by the diffraction pattern of electron diffraction. The crystalline nature of the lithium silicate contained in the second region 122 can be evaluated using the same procedure as when evaluating whether the substance contained in the first region 121 is amorphous. Specifically, the evaluation can be performed using the same procedure, except that the location of the second region 122 is identified by TEM observation instead of the first region 121, and electron diffraction measurements are performed on the second region 122. If crystalline spots are observed in the diffraction pattern for the second region 122 and match the pattern of lithium silicate, for example, if the d values match, it can be identified that the second region 122 contains lithium silicate. Furthermore, it can be identified that the lithium silicate contained in the second region 122 is crystalline.
[0036] The second region 122 possesses lithium-ion conductivity while functioning electrically as an insulating layer. Therefore, even when the coated positive electrode active material 10 of this embodiment is applied to a lithium secondary battery and charged at a high potential, the voltage applied to the first region 121, the positive electrode active material 11, and the solid electrolyte is reduced, preventing the application of high voltage and reducing oxidative decomposition of the solid electrolyte. This prevents the first region 121, the positive electrode active material 11, and the solid electrolyte from decomposing due to the application of voltage, and prevents a decrease in battery capacity even when the lithium secondary battery containing the coated positive electrode active material 10 of this embodiment is charged at a high potential.
[0037] In this specification, "charging at a high potential" means charging by applying a voltage of 4.4V or higher, for example, based on the Li-In alloy potential.
[0038] As described above, the second region 122 may also contain a crystalline phase of lithium silicate. The crystalline nature of lithium silicate particularly enhances the electrical insulation properties of the second region 122, and particularly prevents the first region 121, the positive electrode active material 11, and the solid electrolyte from decomposing due to the application of voltage. (2-2) Regarding the thickness of the coating As shown in Figure 1(A), when the coated positive electrode active material 10A has one layer of coating 12, the thickness T12 of the coating 12 refers to the thickness measured at any position on the coating 12.
[0039] As shown in Figure 1(B), the coating 12 of the coated positive electrode active material 10B has a structure in which a layer of the first region 121 and a layer of the second region 122 are stacked. In this case, the thickness T12 of the coating 12 means the sum of the thicknesses of the first region 121 and the second region 122, measured at any position on the coating 12.
[0040] The thickness T12 of the coating 12 may be, for example, 1 nm or more, 2 nm or more, or 4 nm or more.
[0041] By setting the thickness T12 of the coating 12 to 1 nm or more, when applied to a lithium secondary battery, it is possible to prevent the formation of a high-resistance layer between the positive electrode active material 11 and the solid electrolyte, thereby particularly reducing interfacial resistance. Furthermore, even when applied to a lithium secondary battery and charged and discharged at a high potential, the voltage applied to the first region 121, the positive electrode active material 11, and the solid electrolyte is reduced, and the application of high voltage is particularly prevented. As a result, the decomposition of the first region 121, the positive electrode active material 11, and the solid electrolyte due to the application of voltage is particularly prevented, and the lithium secondary battery containing the coated positive electrode active material 10 of this embodiment is particularly prevented from losing battery capacity even when charged at a high potential.
[0042] The upper limit of the thickness T12 of the coating 12 is not particularly limited, but may be, for example, 100 nm or less, 50 nm or less, or 20 nm or less.
[0043] By setting the thickness T12 of the coating 12 to 100 nm or less, when applied to a lithium secondary battery, the proportion of layers that do not contribute to charging and discharging can be suppressed, thereby significantly increasing the battery capacity.
[0044] Therefore, the thickness T12 of the coating 12 may be 1 nm or more and 100 nm or less, 2 nm or more and 50 nm or less, or 4 nm or more and 20 nm or less.
[0045] The thickness T12 of the coating 12 can be measured at any cross-section of the coated positive electrode active material 10. For example, the thickness T12 of the coating 12 can be measured at any location on the coating 12 in a TEM image of the cross-section. (2-3) Coverage The coverage rate of the coated positive electrode active material 10 in this embodiment can be evaluated using XPS (X-ray Photoelectron Spectroscopy).
[0046] Specifically, it can be calculated using the composition measured using XPS.
[0047] Here, let A be the percentage of elements other than lithium and oxygen contained in the coated positive electrode active material 11, as measured using XPS.
[0048] The molar percentage of silicon (Si) measured using XPS is defined as Si.
[0049] CO2 measured using XPS. 3- The percentage of CO2 in terms of amount of substance 3- Let's assume that.
[0050] Si, CO 3- These components are derived from lithium silicate and lithium carbonate contained in coating 12.
[0051] In this case, the Si coating on the surface of the positive electrode active material 11, calculated using the composition measured by XPS and the following formula (1), may be 30% or more.
[0052] Further, using the composition measured by XPS, calculated by the following formula (2), on the surface of the positive electrode active material 11, CO 3- the coverage may be 50% or more. (Si coverage)=Si÷(Si+A)×100···(1) (CO 3- coverage)=CO 3- ÷(CO 3- +A)×100···(2) Setting the Si coverage to 30% or more means that the second region 122 is sufficiently disposed on the surface of the positive electrode active material 11. Therefore, even when the coated positive electrode active material 10 of the present embodiment is applied to a lithium secondary battery and charged at a high potential, the voltage applied to the first region 121, the positive electrode active material 11, and the solid electrolyte can be reduced, preventing a high voltage from being applied, and the oxidative decomposition of the solid electrolyte can be reduced. Further, it is possible to prevent the first region 121, the positive electrode active material 11, and the solid electrolyte from being decomposed by voltage application, and for the lithium secondary battery including the coated positive electrode active material 10 of the present embodiment, it is possible to prevent the battery capacity from decreasing even when charged at a high potential.
[0053] The Si coverage may be 40% or more, or 45% or more.
[0054] The upper limit of the Si coverage is not particularly limited, and may be 100% or less, 80% or less, or 70% or less.
[0055] Accordingly, the Si coverage may be 30% to 100%, 40% to 80%, or 45% to 70%.
[0056] CO 3- Setting the coverage to 50% or more means that the first region 121 is sufficiently disposed on the surface of the positive electrode active material 11. Therefore, when the coated positive electrode active material 10 of the present embodiment is applied to a lithium secondary battery, the electron conductivity between the positive electrode active material 11 and the solid electrolyte can be increased, and the output characteristics can be enhanced.
[0057] CO 3- The coverage rate may be 70% or more, or 75% or more.
[0058] CO 3- There is no particular upper limit to the coverage rate, but it may be 100% or less, 90% or less, or 85% or less.
[0059] Therefore CO 3- The coverage rate may be 50% to 100%, 70% to 90%, or 75% to 85%. [Solution for forming coating, method for producing positive electrode active material for coated lithium secondary batteries] The method for producing the coated lithium secondary battery positive electrode active material of this embodiment is not particularly limited. Since the method for producing the coated positive electrode active material of this embodiment allows for the production of a coated positive electrode active material according to one aspect of the present disclosure, some previously described matters will be omitted.
[0060] The method for producing the positive electrode active material for a coated lithium secondary battery according to this embodiment may include, for example, a mixed solution formation step, a precursor formation step, and a heat treatment step.
[0061] In the mixed solution formation process, a positive electrode active material 11 having a layered crystalline structure and a coating-forming solution can be mixed to form a mixed solution.
[0062] In the precursor formation process, the mixed solution is dried to form a precursor on the surface of the positive electrode active material, with the coating solution adhering to it.
[0063] In the heat treatment process, the precursor can be heat-treated to produce a coated positive electrode active material for lithium secondary batteries.
[0064] Before describing each step, we will first explain the method for preparing the coating-forming solution used in the mixed solution formation step. (1) Preparation of coating solution In the coating-forming solution preparation step, a coating-forming solution for forming the coating 12 can be prepared.
[0065] The coating-forming solution preparation step allows for the preparation of a coating-forming solution containing silicon alkoxide and lithium alkoxide.
[0066] The coating solution preparation step may include, for example, the following silicon source preparation step and lithium source preparation step. (1-1) Silicon source preparation process In the silicon source preparation process, a silicon source can be prepared by adding alcohol to a silicon alkoxide.
[0067] As the silicon alkoxide, one or more types selected from, for example, silicon tetraethoxide or silicon tetramethoxide can be used.
[0068] As the alcohol, one or more types selected from ethanol, 1-butanol, isobutanol, 2-methoxyethanol, etc., can be used. (1-2) Lithium source preparation process In the lithium source preparation process, a lithium source can be prepared by adding an alcohol to a lithium alkoxide.
[0069] As the alcohol, one or more types selected from ethanol, 1-butanol, isobutanol, 2-methoxyethanol, etc., can be used. (1-3) Mixing process In the mixing process, a silicon source and a lithium source are first mixed to prepare a mixture.
[0070] The mixing ratio of the silicon source and the lithium source is not particularly limited, and the area ratio of the first region 121 and the second region 122 can be selected to be within the required range.
[0071] For example, the mixture may be mixed such that the ratio of the amount of lithium (Li) to silicon (Si) in the mixture (Li / Si) is between 2 and 10, or between 3 and 8.
[0072] Next, a carboxylic acid can be added to the mixture to carry out a chelation reaction. The amount of carboxylic acid added may be such that the ratio of the amount of carboxylic acid to the amount of silicon alkoxide (carboxylic acid / silicon alkoxide) is 0.5 to 4.0, or it may be such that it is 0.5 to 2.0.
[0073] As the carboxylic acid, one or more selected from acetic acid, formic acid, oleic acid, maleic acid, etc., can be used.
[0074] The solution obtained after the chelation reaction may be used as a coating-forming solution. Alternatively, after the chelation reaction, water may be added and mixed at 0°C to 50°C to perform partial hydrolysis and obtain a coating-forming solution. The water may be added so that the ratio of the amount of water to silicon contained in the silicon alkoxide (H2O / Si) is between 0 and 2.0.
[0075] The silicon source and the lithium source may be mixed, and then, if necessary, subjected to chelation or partial hydrolysis, and then further mixed at a temperature above 0°C but below the boiling point of the alcohol used. The boiling point of the alcohol used refers to the boiling points of the alcohols contained in the silicon source and the lithium source. If the silicon source and the lithium source contain different types of alcohols, the boiling point of the alcohol used refers to the boiling point of the alcohol with the lowest boiling point. In addition, the silicon source and the lithium source may be mixed, and then, if necessary, subjected to chelation or partial hydrolysis, and then refluxed at a temperature above the boiling point of the alcohol used.
[0076] The coating-forming solution is a solution used to form a coating, and may contain silicon alkoxide and lithium alkoxide.
[0077] The coating-forming solution may contain carboxylic acids or the like. (2) Mixed solution formation process In the mixed solution formation process, a positive electrode active material having a layered crystalline structure and a coating-forming solution can be mixed to form a mixed solution. The mixing ratio of the positive electrode active material and the coating-forming solution is not particularly limited and can be selected according to the required coating thickness for the coated positive electrode active material.
[0078] The positive electrode active material used in the mixed solution formation process is not particularly limited, and for example, the positive electrode active material described in the section on coated positive electrode active material can be used. (3) Precursor formation step In the precursor formation process, the mixed solution obtained in the mixing process is dried to form a precursor on the surface of the positive electrode active material, with the coating solution attached to it.
[0079] The method for drying the mixed solution is not particularly limited and can be dried by any method, such as spray drying or vacuum drying. (4) Heat treatment process In the heat treatment process, the precursor can be heat-treated to produce a coated positive electrode active material for lithium secondary batteries.
[0080] While the heat treatment conditions in the heat treatment process are not particularly limited, selecting the heat treatment conditions allows for the selection of the crystallinity of the material contained in the first and second regions on the surface of the positive electrode active material.
[0081] In the heat treatment process, the material can be heat-treated in an oxidizing atmosphere at a temperature of, for example, 300°C to 400°C for 1 to 10 hours. By performing the heat treatment process, the moisture and organic solvents contained in the coating placed on the surface of the positive electrode active material are reduced, and a coated positive electrode active material having a coating comprising a first region and a second region is obtained.
[0082] The oxidizing atmosphere can be, for example, an oxygen-containing atmosphere, with an oxygen content of 70% to 100% by volume. The oxidizing atmosphere may be an oxygen-only atmosphere, or a mixed atmosphere of oxygen and an inert gas. As the inert gas, noble gases such as argon and helium, or nitrogen gas, can be used. [Lithium-ion rechargeable battery] The lithium secondary battery of this embodiment may include a positive electrode, a negative electrode, and a solid electrolyte layer. For example, the lithium secondary battery of this embodiment may consist of a positive electrode, a negative electrode, and a solid electrolyte layer.
[0083] Specifically, the lithium secondary battery of this embodiment can have a positive electrode 21, a solid electrolyte layer 22, and a negative electrode 23, as shown in Figure 2, for example, the lithium secondary battery 20. As shown in Figure 2, the solid electrolyte layer 22 can be placed between the positive electrode 21 and the negative electrode 23, and these components can be sealed inside the container 24. The positive electrode 21 and the negative electrode 23 are provided with a positive electrode terminal 211 and a negative electrode terminal 231, respectively, and can be configured to connect to components outside the container 24.
[0084] The following describes each component. (1) Positive electrode The positive electrode may include at least one coated positive electrode active material according to one aspect of this disclosure. The positive electrode may consist only of the coated positive electrode active material according to one aspect of this disclosure, or it may include the coated positive electrode active material according to one aspect of this disclosure along with other positive electrode active materials and a solid electrolyte.
[0085] As the solid electrolyte, one or more types selected from, for example, sulfide-based solid electrolytes, oxide-based solid electrolytes, and polymer electrolytes can be used. The positive electrode may contain, for example, a coated positive electrode active material according to one aspect of this disclosure and a sulfide-based solid electrolyte. In addition to the positive electrode active material and solid electrolyte, the positive electrode may also contain materials such as conductive additives, binders, ionic liquids, and other additives.
[0086] When the positive electrode contains a sulfide-based solid electrolyte, the materials described later can be suitably used as the sulfide-based solid electrolyte. Preferably, the positive electrode contains one or more types of sulfide-based solid electrolytes selected from, for example, argyrodite-type sulfide-based solid electrolytes and Li2S-P2S5-based solid electrolytes. (2) Negative electrode The negative electrode only needs to contain a negative electrode active material; it may consist solely of the negative electrode active material, or it may include both the negative electrode active material and a solid electrolyte.
[0087] As the negative electrode active material, for example, lithium-containing materials such as metallic lithium or lithium alloys, or storage materials capable of intercalating and deintercalating lithium ions can be used. The storage material is not particularly limited, but for example, natural graphite, artificial graphite, calcined organic compounds such as phenolic resins, and carbon materials such as coke can be used. As the solid electrolyte, one or more types selected from sulfide-based solid electrolytes, oxide-based solid electrolytes, and polymer electrolytes can be used. In addition to the negative electrode active material and solid electrolyte, the negative electrode may also contain materials such as conductive additives, binders, ionic liquids, and other additives. (3) Solid electrolyte layer The solid electrolyte layer may contain a lithium-ion conductive solid electrolyte, and may consist only of the solid electrolyte, or it may contain materials such as a binder.
[0088] The solid electrolyte used in the lithium secondary battery of this embodiment is not particularly limited as long as it is a solid electrolyte having lithium ion conductivity. For example, one or more types selected from sulfide-based solid electrolytes, oxide-based solid electrolytes, and polymer electrolytes can be used as the solid electrolyte.
[0089] Examples of sulfide-based solid electrolytes include, but are not limited to, sulfide-based amorphous solid electrolytes, sulfide-based crystalline solid electrolytes, or argyrodite-type solid electrolytes. A specific example of a sulfide-based solid electrolyte is Li 7-x PS 6-x Cl x Solid electrolytes with argyrodite-type structures such as Li7P3S 11 Li2S-P2S5-based solid electrolytes such as Li3PS4, Li8P2S9, Li2S-P2S5-LiI, Li2S-P2S5-LiI-LiBr, and Li2S-P2S5-GeS2(Li 13 GeP3S16 Li 10 GeP2S 12 Examples include, but are not limited to, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, etc., or combinations thereof.
[0090] An example of an oxide-based solid electrolyte is Li7La3Zr2O 12 Li 7-x La3Zr 1-x Nb x O 12 Li 7-3x La3Zr2Al x O 12 Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4-x N x Examples include (LiPON), but are not limited to these.
[0091] Examples of polymer electrolytes include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), and copolymers thereof.
[0092] The solid electrolyte may be glass or crystallized glass (glass ceramic). [Examples]
[0093] The present invention will be described in more detail below with reference to examples, but the present invention is not limited in any way by these examples.
[0094] First, we will explain the evaluation method for lithium secondary batteries using the coated positive electrode active material obtained in the following examples and comparative examples. [Evaluation Method] (1) Floating test The floating test was conducted by preparing and evaluating all-solid-state batteries containing a sulfide-based solid electrolyte using the following method.
[0095] The obtained coated positive electrode active material and sulfide-based solid electrolyte powder (Li6PS5Cl, sulfide-based solid electrolyte with argyrodite structure) were mixed in a mass ratio of coated positive electrode active material:solid electrolyte = 70:30, and this mixture was used as the positive electrode.
[0096] The solid electrolyte layer (separator layer) used the same sulfide-based solid electrolyte powder as that used in the positive electrode. The negative electrode used a lithium-indium alloy prepared by pressing small pieces of lithium foil onto indium foil and diffusing lithium into the indium.
[0097] Then, the positive electrode layer, solid electrolyte layer, and negative electrode layer were stacked in this order and pressure-molded to produce an all-solid-state battery, which is a lithium secondary battery.
[0098] The obtained all-solid-state batteries were charged with a constant current at a current density of 0.1C in a 25°C environment until the cell voltage reached 3.93V (4.55V relative to the Li-In alloy potential). Subsequently, constant voltage charging was performed at a cell voltage of 3.93V until the current density became 0.01C.
[0099] Subsequently, constant current discharge was performed at a current density of 0.1C until the cell voltage reached 2.38V (3.0V relative to the Li-In alloy potential). Then, constant voltage discharge was performed at a cell voltage of 2.38V until the current density became 0.01C. The above charge and discharge operation will be referred to as the initial charge and discharge below. The capacity of the constant current discharge at a current density of 0.1C during this process was defined as the "initial discharge capacity."
[0100] Subsequently, the all-solid-state battery was charged at a constant current of 0.1C in a 25°C environment until the cell voltage reached 3.93V (4.55V relative to the Li-In alloy potential). Then, constant voltage charging was performed at a cell voltage of 3.93V until the current density reached 0.01C. Next, the battery was moved to a 60°C environment and subjected to continuous constant voltage charging (trickle charging) at a cell voltage of 3.93V for 120 hours (floating test).
[0101] The all-solid-state battery was then returned to 25°C, and constant-current and constant-voltage discharge were performed under the same conditions as the initial charge-discharge. After that, charge-discharge was performed under the same conditions as the initial charge-discharge. The capacity during constant-current discharge at this time was defined as the "capacity after floating test." The ratio of the capacity after floating test to the initial discharge capacity was then calculated and defined as the "capacity retention rate after floating." (Example 1) (1) Manufacturing of coated positive electrode active material (1-1) Preparation of coating solution (Silicon source preparation process) In the silicon source preparation process, 2-methoxyethanol was added to silicon tetraethoxide to prepare the silicon source.
[0102] (Lithium source preparation process) In the lithium source preparation process, a lithium source was prepared by adding 2-methoxyethanol to lithium alkoxide. (Mixing process) A mixture was prepared by mixing a silicon source and a lithium source.
[0103] The silicon source and the lithium source were mixed in the coating solution such that the ratio of lithium (Li) to silicon (Si) in substance (Li / Si) was 4.
[0104] Next, acetic acid was added to the mixture to carry out a chelation reaction. The amount of acetic acid added was such that the molar ratio of acetic acid to silicon tetraethoxide (acetic acid / silicon tetraethoxide) was 2, and the mixture was then mixed.
[0105] After mixing, the mixture was refluxed at 125°C for 2 hours to prepare a coating-forming solution. (1-2) Mixed solution formation process Cathode active material powder (LiNi 0.5 Co 0.2 Mn 0.3 A mixed solution was formed by mixing O2 with a coating-forming solution. (1-3) Precursor formation step The resulting mixture was sprayed using a high-speed airflow dispersion device (manufactured by Kawata Co., Ltd.), and by controlling the temperature of the high-pressure airflow supplied to the device, a precursor was formed in which the coating solution was attached to the surface of the positive electrode active material particles. (1-4) Heat treatment process A coated cathode active material having a coating on its surface was prepared by heat-treating the precursor in an oxygen atmosphere at 300°C for 1 hour and then drying it. (2) Evaluation of coated positive electrode active material (2-1) Presence or absence of covering SEM and cross-sectional TEM images of the obtained coated cathode active material were observed.
[0106] The SEM images were used to observe the surface of the coated positive electrode active material, and EDX was used to observe the distribution of elements contained in the coating. SEM images were observed at 2000x and 5000x magnification.
[0107] In addition to the SEM image, the cross-sectional TEM image confirmed that a single layer of coating 12 was present on the surface of the positive electrode active material 11. Furthermore, it was confirmed that the coating 12 contained two different regions with distinct structures.
[0108] Electron diffraction revealed that the first region contained amorphous material, as no crystal spots were observed. Furthermore, EDX measurements were performed on the first region, and based on the elements contained in the first region and their proportions, it was determined that it contained lithium carbonate.
[0109] Electron diffraction was performed on the second region, which has a different appearance from the first region, and crystal spots were observed, confirming that it possesses crystalline properties. Furthermore, the observed d-value confirmed that the crystalline material is lithium silicate.
[0110] If the first region is identified, a "○" is entered in the "First Region" column under "Coverage" in Table 1. If the second region is identified, a "○" is entered in the "Second Region" column under "Coverage" in Table 1.
[0111] The thickness of coating 12 was determined from the TEM image. (2-2) Coverage Using XPS, the surface composition of the coated positive electrode active material is measured, and the Si coating and CO are determined using the previously described equations (1) and (2). 3- The coverage rate was calculated. (2-3) Floating Test Using the obtained coated positive electrode active material, an all-solid-state battery was fabricated and a floating test was performed. The evaluation results are shown in Table 1. (Example 2) (1) Manufacturing of coated positive electrode active material In the "(1-1) Preparation of coating solution step" (mixing step), acetic acid was added and mixed so that the molar ratio of acetic acid to silicon tetraethoxide (acetic acid / silicon tetraethoxide) was 0.5. Except for the above, the coated cathode active material was prepared and evaluated under the same conditions as in Example 1.
[0112] Observation of SEM and cross-sectional TEM images confirmed that a single layer of coating 12 was present on the surface of the positive electrode active material 11. Furthermore, two regions were identified within the coating 12. The first region was found to contain amorphous lithium carbonate, while the second region was found to contain crystalline lithium silicate.
[0113] The evaluation results are shown in Table 1. (Comparative Example 1) The positive electrode active material powder (LiNi) subjected to the mixed solution formation process 0.5 Co 0.2 Mn 0.3 O2) was used as the positive electrode active material in Comparative Example 1, and the preparation steps for the coating-forming solution were not performed; in other words, no coating was formed.
[0114] The positive electrode active material was evaluated using the same procedure as in Example 1. The evaluation results are shown in Table 1. (Comparative Example 2) (1) Manufacturing of coated positive electrode active material The "(Silicon Source Preparation Step)" in "(1-1) Preparation of Coating Forming Solution" was not performed, and the lithium source obtained in "(Lithium Source Preparation Step)" was used as the coating forming solution.
[0115] Except for the points mentioned above, the coated positive electrode active material was prepared and evaluated under the same conditions as in Example 1.
[0116] Cross-sectional TEM images revealed that only the first region was visible. Furthermore, it was confirmed that the first region contained amorphous material and lithium carbonate.
[0117] The evaluation results are shown in Table 1. (Comparative Example 3) (1) Manufacturing of coated positive electrode active material In the mixing process, water was added to the mixture to perform partial hydrolysis and prepare a coating-forming solution. That is, partial hydrolysis was performed without adding acetic acid. The obtained coating-forming solution was used in the "(mixed solution formation process)".
[0118] Except for the points mentioned above, the coated positive electrode active material was prepared and evaluated under the same conditions as in Example 1.
[0119] Cross-sectional TEM images revealed that only the second region was visible. Furthermore, it was confirmed that the second region contained crystalline lithium silicate.
[0120] The evaluation results are shown in Table 1.
[0121] [Table 1] As shown in Table 1, the lithium secondary batteries using the coated positive electrode active materials of Examples 1 and 2, in which the coating has a first region and a second region, were confirmed to have a capacity retention rate of 90% or more after the floating test. In other words, it was confirmed that this can be applied to all-solid-state batteries and that the decrease in battery capacity can be suppressed even when charged at high potential.
[0122] The aspects of this disclosure are, for example, as follows:
[0123] (1) A coated lithium secondary battery positive electrode active material for use in the positive electrode of an all-solid-state battery, wherein the electrolyte is a solid electrolyte, It comprises a positive electrode active material having a layered crystalline structure and a coating disposed on the surface of the positive electrode active material, The coating comprises a first region containing lithium carbonate and a second region containing lithium silicate, wherein the coating is a coated positive electrode active material for a lithium secondary battery.
[0124] (2) The first region comprises an amorphous phase of lithium carbonate, The positive electrode active material for a coated lithium secondary battery according to (1), wherein the second region includes a crystalline phase of lithium silicate.
[0125] (3) The coated positive electrode active material for lithium secondary batteries according to (1) or (2), wherein the thickness of the coating is 1 nm or more.
[0126] (4) The Si coating on the surface of the positive electrode active material, calculated using the composition measured by XPS, is 30% or more, and the CO coating on the surface of the positive electrode active material is 30% or more. 3- A coated lithium secondary battery positive electrode active material according to any of (1) to (3), wherein the coating rate is 50% or more.
[0127] (5) A coating-forming solution containing silicon alkoxide and lithium alkoxide.
[0128] (6) A method for producing a positive electrode active material for a covered lithium secondary battery used in the positive electrode of an all-solid-state battery, wherein the electrolyte is a solid electrolyte, A mixed solution formation step involves mixing a positive electrode active material having a layered crystalline structure with the coating-forming solution described in claim 5 to form a mixed solution, A precursor formation step involves drying the mixed solution to form a precursor on the surface of the positive electrode active material in which the coating-forming solution is attached, The process includes a heat treatment step of heat-treating the precursor to produce a coated lithium secondary battery positive electrode active material, The coated lithium secondary battery positive electrode active material has a coating disposed on the surface of the positive electrode active material. A method for producing a coated positive electrode active material for a lithium secondary battery, wherein the coating comprises a first region containing lithium carbonate and a second region containing lithium silicate.
[0129] (7) Having a positive electrode, a negative electrode, and a solid electrolyte layer, A lithium secondary battery wherein the positive electrode comprises a coated lithium secondary battery positive electrode active material described in any of (1) to (4) and a sulfide-based solid electrolyte.
[0130] (8) The lithium secondary battery according to (7), wherein the sulfide-based solid electrolyte comprises one or more selected from argyrodite-type sulfide-based solid electrolytes and Li2S-P2S5-based solid electrolytes. [Explanation of Symbols]
[0131] 10. Coated positive electrode active material (coated positive electrode active material for lithium secondary batteries) 10A Coated Positive Electrode Active Material (Coated Positive Electrode Active Material for Lithium-ion Secondary Batteries) 10B Coated Positive Electrode Active Material (Coated Positive Electrode Active Material for Lithium-ion Secondary Batteries) 11 Cathode active material 12 Covering 121 1st area 12B 2nd area T12 Thickness 20 Lithium-ion rechargeable batteries 21 Positive electrode 211 Positive terminal 22 Solid electrolyte layer 23 Negative electrode 231 Negative terminal 24 Container
Claims
1. A coated lithium secondary battery positive electrode active material used in the positive electrode of an all-solid-state battery, in which the electrolyte is a solid electrolyte, It comprises a positive electrode active material having a layered crystalline structure and a coating disposed on the surface of the positive electrode active material, The coating comprises a first region containing lithium carbonate and a second region containing lithium silicate, wherein the coating is a coated positive electrode active material for a lithium secondary battery.
2. The first region comprises an amorphous phase of lithium carbonate. The positive electrode active material for a coated lithium secondary battery according to claim 1, wherein the second region includes a crystalline phase of lithium silicate.
3. The coated positive electrode active material for a lithium secondary battery according to claim 1 or claim 2, wherein the thickness of the coating is 1 nm or more.
4. The Si coating on the surface of the positive electrode active material, calculated using the composition measured by XPS, is 30% or more, and the CO coating on the surface of the positive electrode active material is 30% or more. 3- A coated lithium secondary battery positive electrode active material according to claim 1 or claim 2, wherein the coating rate is 50% or more.
5. A coating-forming solution containing silicon alkoxide and lithium alkoxide.
6. A method for producing a coated lithium secondary battery positive electrode active material used in the positive electrode of an all-solid-state battery, in which the electrolyte is a solid electrolyte, A mixed solution formation step involves mixing a positive electrode active material having a layered crystalline structure with the coating-forming solution described in claim 5 to form a mixed solution, A precursor formation step involves drying the mixed solution to form a precursor on the surface of the positive electrode active material in which the coating-forming solution is attached, The process includes a heat treatment step of heat-treating the precursor to produce a coated lithium secondary battery positive electrode active material, The coated lithium secondary battery positive electrode active material has a coating disposed on the surface of the positive electrode active material. A method for producing a coated positive electrode active material for a lithium secondary battery, wherein the coating comprises a first region containing lithium carbonate and a second region containing lithium silicate.
7. It has a positive electrode, a negative electrode, and a solid electrolyte layer, A lithium secondary battery wherein the positive electrode comprises a coated lithium secondary battery positive electrode active material according to claim 1 or claim 2 and a sulfide-based solid electrolyte.
8. The sulfide-based solid electrolyte is an argyrodite-type sulfide-based solid electrolyte and Li 2 S-P 2 S 5 A lithium secondary battery according to claim 7, comprising one or more selected from a solid electrolyte system.
Citation Information
Patent Citations
Electrode and method of manufacturing the same, and lithium ion secondary battery
JP2009193940A